Sociolinguistic causes of language change - Grechykhina, N.; Timoshenko, Т.; Гречихіна, Н. В.; Тимошенко, Т. В. (КНТУ, 2011)
Sociolinguistic causes of language change are considered in this article. It deals with three proposed external sociolinguistic factors – fashion, foreign influence and social need which can potentially affect the language and accelerate hidden trends already existing in the language. В статті розглядаються соціолінгвістичні причини зміни мови. Пропонується розгляд трьох зовнішніх соціолінгвістичних факторів – мода, іноземний вплив та соціальна потреба, які можуть потенціально впливати на мову та розвивати вже існуючі у мові приховані тенденції.
Соціолінгвістичні причини зміни мови
Keywords: sociolinguistic factors; fashion; pronunciation; accent; fluctuation theory; substratum theory; adopted language; foreign influence; bilingual; trilingual; borrowing; syntax; cultural contract; donor language; social need; conversion; accelerating agents